Investigasi Pencatatan dan Pelaporan Keuangan UMKM: Apakah Disusun Berdasarkan Standar Akuntansi? - Syamsul, Syamsul (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2024)
This study explores the system, objectives, and compatibility of MSME financial recording and reporting with accounting standards, as well as the obstacles faced by MSMEs in implementing them. This research was conducted in Palu City. The research data was obtained through interviews with MSME actors. Data were analyzed using qualitative descriptive data analysis techniques. The results of the analysis show that MSMEs have not yet implemented a complete financial recording and reporting system. This research also shows that the purpose of MSMEs in recording and reporting business finances is to find out merchandise inventory, business income, business turnover, business capital, business profit/loss, and business performance. In addition, MSME financial recording and reporting is not in accordance with accounting standards. Then, the main obstacle faced, so that they do not record and report MSME finances, is due to a lack of knowledge about financial recording and reporting.